2021
DOI: 10.1371/journal.ppat.1009837
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR-224 contributes to hemolymph microbiota homeostasis during bacterial infection in crustacean

Abstract: It is well known that exosomes could serve as anti-microbial immune factors in animals. However, despite growing evidences have shown that the homeostasis of the hemolymph microbiota was vital for immune regulation in crustaceans, the relationship between exosomes and hemolymph microbiota homeostasis during pathogenic bacteria infection has not been addressed. Here, we reported that exosomes released from Vibrio parahaemolyticus-infected mud crabs (Scylla paramamosain) could help to maintain the homeostasis of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…To date, there are only a few reports on the function of ECSIT gene in invertebrates, namely, two shrimp ECSITs from M. japonicus and Exopalaemon carinicauda (26,47), one mollusk ECSIT from Crassostrea hongkongensis (48), one mud crab ECSIT from Scylla paramamosain, and one Drosophila ECSIT (32,49). Our previous research and the data in this article showed that shrimp ECSIT was necessary for antibacterial signal transduction from MjToll3 to Dorsal.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…To date, there are only a few reports on the function of ECSIT gene in invertebrates, namely, two shrimp ECSITs from M. japonicus and Exopalaemon carinicauda (26,47), one mollusk ECSIT from Crassostrea hongkongensis (48), one mud crab ECSIT from Scylla paramamosain, and one Drosophila ECSIT (32,49). Our previous research and the data in this article showed that shrimp ECSIT was necessary for antibacterial signal transduction from MjToll3 to Dorsal.…”
Section: Discussionmentioning
confidence: 68%
“…Additionally, ECSIT was also located in the mitochondrial complex I, and implicated in complex stability and mitochondrial and cellular reactive oxygen species production during bacterial infection, thus contributing to the bactericidal activity of macrophages (52). In arthropods, the interaction of TRAF6 with ECSIT and their role in regulating the expression of AMPs are reported in Drosophila and mud crab (32,49). However, the functional connection of ECSIT and Toll receptors is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Crustacean seems possess less phagocytic cells compared with other species, which may be due to its unique endosymbiosis with microbes in its hemolymph, which has been partially unveiled by recent studies (Gong et al, 2021;Zheng et al, 2021) Crustacean hemocytes have been classified into hyalinocytes, semi-granulocytes and granulocytes based on morphology and function for the past decades (Soderhall, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In human, most of myeloid cells including monocyte, macrophage, dendritic cell, and neutrophil could engulf pathogens(Bassler et al, 2019). Crustacean seems possess less phagocytic cells compared with other species, which may be due to its unique endosymbiosis with microbes in its hemolymph, which has been partially unveiled by recent studies(Gong et al, 2021; Zheng et al, 2021)…”
Section: Discussionmentioning
confidence: 99%
“…Drosophila Schneider 2 (S2) cells (Invitrogen), a cell line that is widely used in marine invertebrate-related research ( 57 , 58 ), were cultured at 27°C in Express Five serum-free medium (SFM) (Invitrogen). Then, the constructed pIZ/V5 plasmid combinations bearing a Flag or HA tag were cotransfected into S2 cells using the Cellfectin II reagent (Invitrogen, USA).…”
Section: Methodsmentioning
confidence: 99%